ALDRED, Joe (ed.). Pentecostals and Charismatics in Britain: An Anthology. (9th September 2020) - Nyanni, Caleb
Abstract : ALDRED, Joe (ed.). Pentecostals and Charismatics in Britain: An Anthology. London: SCM, 2019. 221pp. Pbk. ISBN 9780334057116. £30.